Economic Development and the World Trade Organization After Doha - Hoekman, Bernard M. (World Bank, Washington, D.C., 2013)
The author analyzes what actions could be taken in the context of the World Trade Organization's Doha negotiations to assist countries in reaping benefits from deeper trade integration. He discusses the policy agenda that confronts many developing countries and identifies a number of focal points that could be used both as targets and as benchmarks to increase the likelihood that WTO negotiations will support development. To achieve these targets, the author proposes a number of negotiating modalities for both goods and services-related market access issues, as well as rule-making in regulatory areas. Throughout the analysis, the author refers to the work of J. Michael Finger, whose numerous writings in this area have not only greatly influenced the thinking of policymakers and researchers on the interaction between trade policy, economic development, and the GATT/WTO trading system, but also provides a model for how to pursue effective policy research.